Complaints against the Slovenian police - Flander, Benjamin (Varstvoslovje, 2020)
Purpose: The paper focuses on the problem of independence and impartiality of the complaints procedure against police work in Slovenia. Relying on the findings of the targeted research project, we address and examine the concerns regarding the adequacy of the current format and indicate the possibilities for legislative changes and reform. Design/Methods/Approach: We carried out an analysis of the legal regulation of the complaints procedure regarding the work of police officers and the results of previous research in the field. Based on the findings, we conducted a structured interview with a general questionnaire in written form and oral interviews with the people who perform the complaints procedures. Findings: The current regulation of complaints has advantages and disadvantages. According to the interviewees and in line with a wider professional consensus, complaints procedures should in future be carried out outside the Ministry of the Interior ("the Ministry") and the police. This would mean that complaints procedures would gain what they lack at present, namely the appearance of impartiality and formal/institutional independence. Research Limitations/Implications: In our research, we interviewed employees of the Ministry and representatives of the public who are involved in proceedings before the complaints panels of the Ministry. In future research, other participants (e.g. the complainants and police officers) should also be interviewed for a more comprehensive view of the issue. Originality/Value: We examined the views of the employees of the Ministry who carry out complaints procedures in order to establish the validity of concerns regarding the adequacy of current regulation and we indicated the possibilities for reform of the current procedures.
Keywords: complaints against police work; impartiality; independence; neodvisnost; nepristranskost; postopek; pritožba zoper delo policije; procedure; Slovenia; Slovenija